Bio‐Polypropylene and Polypropylene‐based Biocomposites: Solutions for a Sustainable Future. Issue 2 (3rd December 2022) - Wang, Suxi; Muiruri, Joseph Kinyanjui; Soo, Xiang Yun Debbie; Liu, Songlin; Thitsartarn, Warintorn; Tan, Beng Hoon; Suwardi, Ady; Li, Zibiao; Zhu, Qiang; Loh, Xian Jun
Abstract: Polypropylene (PP) is among the most widely used commodity plastics in our everyday life due to its low cost, lightweight, easy processability, and exceptional chemical, thermo‐mechanical characteristics. The growing awareness on energy and environmental crisis has driven global efforts for creating a circular economy via developing sustainable and eco‐friendly alternatives to traditional plastics produced from fossil fuels for a variety of end‐use applications. This review paper presents a brief outline of the emerging bio‐based PP derived from renewable natural resources, covering its production routes, market analysis and potential utilizations. This contribution also provides a comprehensive review of the PP‐based biocomposites produced with diverse green fillers generated from agro‐industrial wastes, with particular emphasis on the structural modification, processing techniques, mechanical properties, and practical applications. Furthermore, given that the majority of PP products are currently destined for landfills, research progress on enhancing the degradation of PP and its biocomposites is also presented in light of the environmental concerns. Finally, a brief conclusion with discussions on challenges and future perspectives are provided. Abstract : Fossil fuel depletion and environmental contamination are the two major issues facing commodity plastics. This review provides an overview of recent advancements in the eco‐friendly substitutes to conventional polypropylene (PP), including bio‐based PP and PP‐biocomposites, highlighting structure modification techniques, processing methods, mechanical performance, applications as well as their degradation behaviors.